Strategi Pemecahan Masalah Learning Loss pada Peserta Didik Setelah Pandemi COVID-19 di SMA Negeri 5 Kupang - Marius F. Naga (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2023)
This study aimed to find out the strategy of problem-solving conducted at SMA Negeri 5 Kupang. This research uses qualitative methods. The subjects in this study were students at SMA Negeri 5 Kupang. Data collection techniques through observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation, and conclusions. The results of this research show that the strategy for solving the problem of learning loss among students after the COVID-19 pandemic at SMA Negeri 5 is that teachers can use methods that can be applied without having to gather and have physical contact, such as inquiry methods, case studies, problem-solving, recitation, and so on. By interacting a lot, it is hoped that it can help strengthen students' communication skills and create emotional closeness between fellow students and the teacher.